Yield and zinc uptake in rice (Oryza sativa) as influenced by sources and times of zinc application - KARAK, TANMOY; DAS, D K; MAITI, DEBTANU (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during winter season of 1999-2001 'IET-4094' rice (Oryza sativa L.) in an Aeric Haplaquept (pH 6.80, organic C 5.3 g/kg, DTPA extractable Zn 0.51 mg/kg), to study the effect of soil application of Zn on the yield and Zn content of rice. The results showed that the amount of Zn content in rice dry matter recorded an increase (9.42 mg/kg) with the application ofchelated Zn (Zn-EDTA) in 2 splits compared to split application ofZnS04 (8.56 mg/kg). The amount ofZn content and uptake ofgrain and straw were found highest in the treatment where corelated Zn (Zn-EDTA) was applied as splits. The yield of rice grain was recorded highest (4.56 tonnes/ha) in the treatnlent receiving split application ofchelated zinc. The yield ofgrain and straw was significantly positively correlated with their corresponding Zn content (r=0.905* and r=O.929**) respectively.